Hydromechanics – Slope Monitoring in Rainy Season - Agus Setyo Muntohar; Ani Hairani; Muhammad Fikri Permana; Farid Nur Bahti (Civil Engineering Dimension, 2023)
Rainfall and soil response are necessary to be monitored to have slope characteristics in detecting landslide occurrence. Even though much research has been carried out worldwide for rainfall monitoring, less research has been conducted in Indonesia for slope monitoring. Therefore, this research was conducted to observe the suction, soil moisture content, and rainfall in a silty sand slope. An automatic rain gauge was set on the ground to measure precipitation. Tensiometer and soil moisture content sensors were installed at depths of 0.5 m; 1 m; and 1.5 m from the slope surface. The monitoring was conducted during the peak rainy season from December 2022 to January 2023. The rainfall amount is about 436.6 mm, and the 6 hours of rainfall events contribute a relatively sizeable rainfall amount (about 31%) to the total. The safety factor of the slope is estimated to decrease by 39%-40% due to the rainfall.